Universal voice compression algorithms based on approximate string matching - Sadeh, Ilan; Keizelman, Alexander; Zak, Michael (Zielona Góra: Uniwersytet Zielonogórski)
Two practical voice-coding schemes based on approximate string matching are proposed. The first one is an approximate fixed-length string-matching data compression, and the other is a Lempel-Ziv-type quasi-parsing method by approximate string matching. The performance of the two algorithms and their sub-optimal versions are evaluated. The main advantages of the proposed methods are the asymptotic sequential behaviour of the encoder and the simplicity of the decoder. In particular, a sub-optimal tree-structure algorithm is proposed and its real-time advantages are demonstrated.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka